Exploring al-Shāfi'ī and Hanafī Perspectives on Local Beliefs: The Sacred Status of Karaeng Lolo Bayo's Shrine in Sanrobone, Indonesia - Hasanuddin, Muhammad Irfan; Rahmadani (Mazahibuna: Jurnal Perbandingan Mazhab, 2023)
The increasing belief of the Sanrobone community in the sanctity of Karaeng Lolo Bayo's Tomb is rooted in the significant contributions made while alive, and the deep influence has cultivated a lasting sense of reverence among its members. Therefore, this research was conducted to report the public belief in the sacred grave of Karaeng Lolo Bayo within the Sanrobone community. The belief was subject to analysis through a comparative examination of the two main schools of Islamic fiqh, Hanafiyah and al-Shafi'iyah, specifically concerning the pilgrimage activities associated with the grave. Primary data collection was conducted using interviews with several community leaders, visitors, and experts in related fields. Meanwhile, observation and documentation were used to analyze the data obtained through the interview method. The results showed that the tradition of grave pilgrimage in the Sanrobone community serves the purpose of honoring their ancestors and enabling community members to engage in prayer rituals at the gravesite. The al-Shafi'i madhhab and the Hanafi madhhab literature permitted this tradition in line with the fundamental principles of Islam, maintained simplicity, and avoided acts associating partners with Allah.